Microscopic pore structure characteristics and implications of deep coal measure reservoirs in eastern Ordos Basin - MA Litao, WU Peng, YANG Jianghao, HU Weiqiang, HUANG Ying, LIU Cheng, NIU Yanwei, WANG Zhizhuang, REN Dazhong (Youqicang pingjia yu kaifa)
The deep coalbed methane resources in the eastern Ordos Basin are abundant, and comprehensive development of coal measure gas can enhance resource utilization and improve single well gas production. To precisely identify the “sweet spot layer,” this study compares the pore development characteristics of coal measure mudstone, coal rock and tight sandstone in the Shan 2 Section of the Shanxi Formation in the eastern Ordos Basin using organic geochemical analysis, dual-beam scanning electron microscopy, high-pressure mercury intrusion, low-temperature N2 adsorption, and low-temperature CO2 adsorption tests. The results show that clay mineral content is the main factor influencing pore development in coal measure mudstone and tight sandstone. The microscopic pore structure of coal measure reservoirs exhibits significant variations: mudstones and tight sandstones are characterized by mesopores (2-50 nm) within clay minerals, with their mesopore-specific surface area and pore volume being roughly equal. Coal develops abundant micropores (<2 nm) in organic nanopores, with a micropore-specific surface area far exceeding the mesopore-specific surface area of mudstone and tight sandstone. Tight sandstone also develops numerous macropores (>50 nm) in clay mineral pores and microfractures, exhibiting better connectivity than mudstone. Tight sandstone provides substantial storage space for free gas, while the pores in mudstone and coal can adsorb a large amount of natural gas. The sand-mud-coal and sand-coal combinations are the main exploration targets for coal measure strata.